Differential impacts of maternal and paternal attachments on adolescent delinquency: implications for counselling - Manouchehri, Mahshid; Harun, Maizatul Mardiana; Baber, Carrie (Universiti Putra Malaysia, 2024)
Delinquency among adolescents is a growing concern in Iranian society. Research on the role of maternal and paternal attachments, particularly in the Iranian context, has received limited attention. This correlational study aims to concurrently investigate the predictive capacity of both maternal and paternal attachment on delinquent behaviours among Iranian adolescents. The sample included 528 students aged 15 and 17 from 10 government high schools in Tehran who were selected using multi-stage cluster sampling. Participants completed self-administered questionnaires using two established instruments. The findings highlighted a significant association between high parental attachment scores and low adolescent delinquent activity. Secure attachments to mothers and fathers were found to reduce engagement in delinquency. Adolescent age, fathers’ educational level, and maternal attachment emerged as significant predictors of delinquency. Adolescents with insecure maternal attachments and older adolescents with educated fathers showed greater susceptibility to delinquent behaviour. The study also emphasises the vast contribution of mothers to adolescent development, suggesting the need for further exploration of paternal influence on internal dynamics and delinquency in future research. In a broader sense, understanding the differential impacts of these attachments on adolescent delinquency may help counsellors to effectively address these issues and provide appropriate interventions.